En jämförelse på beståndsnivå kring snö och vindskador hos Pinus contorta latifolia och Pinus sylvestris i norra Sverige - Haapalahti, Mari (Linnéuniversitetet, Institutionen för skog och träteknik (SOT), 2020)
Pinus Contorta was introduced to Sweden as a tree that would grow fast with a promising future, also a promise in increased production. What could not be anticipated was the common Swedish weather conditions, such as snow and wind, would have negative impact on Pinus contorta due to its instability connected to fast-growing trunk and wide crown. Those predictions were hard to estimate since these weather conditions also is common in Canada, where it has its origins. The overall damage caused by snow and wind generates an annual loss of approximately hundred million Swedish crowns (SEK), which has a great impact on the Swedish forestry economy. The awareness of the risks and damages on Pinus contorta makes it possible to both prevent and avoid these to some extent. A more detailed study has been done in the Swedish region Norrbotten, where the level of the damage on Pinus contorta was compared to the Swedish pine. The study included inventory of un-thinned stands and quantified data was collected. The conclusions indicated that the level of damage on Pinus contorta stands was more than twice the damage of the Pinus sylvestris stands. However, since Pinus contorta is relatively new in Sweden, the results regarding the future of the contorta pine are therefore insufficient. Furthermore, it is not possible to predict if the promised increase of production will ever be achieved. To achieved reliable results, further studies are suggested where both loss of profit, compared to the Pinus sylvestris stands, but also the full turnaround time of Pinus contorta are included.